Multidimensional Analysis of Acceptance of the Policy of Religious Moderation: A Study of UIN Students in Bandung and Banten - Bambang Qomaruzzaman; Abdul Hanan; Azkia Febi Adhiani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study explores the acceptance of religious moderation policies among university students in Indonesia, focusing on its implementation in UIN Sunan Gunung Djati Bandung and UIN Sultan Maulana Hasanuddin Banten. Using a mixed-methods approach, the research combines quantitative surveys (N=382) and qualitative interviews with students and faculty. The quantitative data analyze multiple dimensions, including trust in institutions, satisfaction with implementation, perceived benefits, legitimacy, transparency, and equity. The qualitative findings provide contextual insights into challenges such as lack of flexibility and limited information access. Results show that while students generally support religious moderation policies due to their alignment with religious and cultural values, there are notable gaps in transparency and flexibility. The findings align with policy acceptance theories, suggesting that trust in institutions, tangible benefits, and inclusive engagement significantly enhance acceptance. The study concludes with recommendations for improving policy outreach and contextual relevance to foster wider acceptance among students.